Human trafficking for labour exploitation: The survivors’ perspective - Villacampa Estiarte, Carolina (International review of victimology, 2024)
Despite being the second most prevalent form of human trafficking, human trafficking for labour exploitation remains a victimisation process that has received little scholarly attention. This qualitative study, based on data from in-depth interviews with labour trafficking survivors in Spain, seeks to apprehend how they experienced that situation while giving them a voice and adopting a survivor-centric approach to the phenomenon. To this end, it first analyses from their perspective the process of their enslavement, as well as the feelings it engendered: from recruitment, to transfer, to exploitation, including the objective circumstances and means used. It then analyses the essential aspects of the process leading to their liberation, examining how the situation was ended, the type of assistance received and desired, and the recourse they had to a criminal law response. It concludes with a series of proposals for how labour trafficking should be institutionally addressed in view of the survivors’ suggestions.